Slovakia Prior to Joining the Euro-Atlantic Structures. Getting Ready for NATO and the EU: Political, Economic and Social Aspects (Czech Journal of International Relations, 2004)
Drawing upon earlier work by the author, the text seeks to help answeringthe question of the sources of fear regarding the future integration ofSlovakia. By looking at the roots and substance of this fear, the author aimsto evaluate whether it has become unsubstantiated since the 2002 generalelection. Even though Dzurinda's 1998 government has fallen short of thevoters' expectations, this has never been true in the foreign and securitypolicy where the government delivered on its promises. The first chapteraims to identify the key factors, having the greatest effect on the policy- anddecision-making of Slovakia's political elite between 1998 and 2002. Thesefactors have been crucial in extending the country's image as being themost problematic out of the Visegrad group. The second chapter deals withSlovakia's internal political watershed: the 1998 general election. Theproblems weakening and ultimately threatening the ruling coalition fromwithin are analysed as well. The third chapter discusses economic andsocial aspects of Slovakia's post-1998 domestic development. The ratherunbalanced performance and the lack of achievements are examined as thecauses of doubts about the translation of Slovakia's integration ambitionsinto practical outcomes. Finally, the last chapter describes the societalperceptions in Slovakia as reflected in public opinion polls prior to the 2002general election, summing up the election results. In answer to thequestion posed at the beginning, the author closes his analysis claimingthat the current level of preparations for Slovakia's integration into both theEuropean and Trans-Atlantic structures guarantees that the country willsuccessfully join both. Despite the lack of any bullet-proof guarantee of thestability of the country's post-2002 political scene, and in spite of potentialchange of the government or early elections, Slovakia's full integration intothe European and Euro-Atlantic institutional structures in mid-2004 cannotbe prevented. Slovakia will join along with its Visegrad partners.